2016
DOI: 10.1016/j.ajpath.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor and Its Ligands Inhibit Myofibroblast Formation and Activation

Abstract: Thyroid eye disease (TED) is a degenerative disease that manifests with detrimental tissue remodeling, myofibroblast accumulation, and scarring in the orbit of affected individuals. Currently, there are no effective therapies for TED that target or prevent the excessive tissue remodeling caused by myofibroblast formation and activation. The canonical cytokine that induces myofibroblast formation is transforming growth factor (TGF)-b. The TGF-b signaling pathway is influenced by aryl hydrocarbon receptor (AHR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 51 publications
(58 reference statements)
0
41
0
Order By: Relevance
“…Ahr −/− EAU mice also display higher protein expression levels of the M1 marker subset, inducible nitric oxide synthase (iNOS) and CD16, and lower protein expression levels of the M2 marker subset, arginase-1 (Arg-1) and CD206, relative to Ahr +/+ EAU mice [129]. Finally, AHR agonists ITE and FICZ have been shown to prevent TGFβ-induced myofibroblast formation in fibroblasts, specifically via inhibiting the β-Catenin/Wnt signaling, leading to the regulation of contractility and proliferation of the human orbital fibroblasts isolated from patients with thyroid eye disease [130]. All in all, though investigating the AHR in the eye is a relatively new area of research, the studies so far indicate that this receptor is involved in modulation of pathogenic pathways, which regulate several retinal diseases (Figure 3) and should be considered as a potential druggable target for the treatment of such maladies.…”
Section: The Ahr and Ocular Diseasesmentioning
confidence: 99%
“…Ahr −/− EAU mice also display higher protein expression levels of the M1 marker subset, inducible nitric oxide synthase (iNOS) and CD16, and lower protein expression levels of the M2 marker subset, arginase-1 (Arg-1) and CD206, relative to Ahr +/+ EAU mice [129]. Finally, AHR agonists ITE and FICZ have been shown to prevent TGFβ-induced myofibroblast formation in fibroblasts, specifically via inhibiting the β-Catenin/Wnt signaling, leading to the regulation of contractility and proliferation of the human orbital fibroblasts isolated from patients with thyroid eye disease [130]. All in all, though investigating the AHR in the eye is a relatively new area of research, the studies so far indicate that this receptor is involved in modulation of pathogenic pathways, which regulate several retinal diseases (Figure 3) and should be considered as a potential druggable target for the treatment of such maladies.…”
Section: The Ahr and Ocular Diseasesmentioning
confidence: 99%
“…However, it was unclear if this beneficial response was dependent upon the AHR itself, as some ligands have independent functions. More recently, we found that the AHR ligand 6-formylindolo[3,2-b]carbazole (FICZ) is also effective against TGFβ-induced myofibroblast formation and collagen production in TED fibroblasts and normal orbital fibroblasts [9]. Importantly, this study demonstrated for the first time that the AHR pathway is critical in preventing myofibroblast formation in TED patient fibroblasts.…”
Section: Introductionmentioning
confidence: 80%
“…Importantly, this study demonstrated for the first time that the AHR pathway is critical in preventing myofibroblast formation in TED patient fibroblasts. Further investigation of the mechanism behind FICZ action revealed that the Wnt/β-catenin signaling pathway is critical, and signaling through this pathway was dependent on the AHR [9]. AHR is a ligand-dependent transcription factor with a large binding pocket suggesting there is the opportunity to identify diverse and structurally selective activating ligands [10,11], which could be investigated as potential therapeutics for TED.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl hydrocarbon receptor is widely distributed in the intestine and immune cells, 28,29 and has been implicated in the pathogenesis of inflammation and thyroid eye disease. 30,31 With regard to pancreatic β-cells and insulin secretion, ARNT (a heterodimerization partner for AhR) was reported to play a critical role in maintaining insulin release from pancreatic β-cells. 32 It is not yet clear how AhR is secreted from the cells or what the correlation is between tissue and serum AhR concentrations.…”
Section: Discussionmentioning
confidence: 99%